2018
DOI: 10.1186/s12905-018-0663-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with modern contraceptive discontinuation among reproductive age group women, a community based cross-sectional study in Humera town, northern Ethiopia

Abstract: BackgroundContraceptive prevalence rate (CPR) for married women aged 15–49 in Ethiopia is 36%, with 35% using modern methods and 1% using traditional methods. However, the discontinuation rate is fairly high. Women usually discontinue contraception use for fertility and method related reasons without adopting an alternate method which in turn leads to many health risks such as unwanted pregnancy, unplanned childbearing, miscarriage, abortion, leads to morbidity and mortality among mothers and newborns. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 5 publications
8
36
1
Order By: Relevance
“…In this study, the 12-month contraceptive discontinuation rate among women age 15–49 who started an episode of contraceptive use within the 5 years before the MDHS was 39% for all methods., This rate was consistent with the average 12-month discontinuation rate (38%) in 25 other low and middle income countries [ 13 ]. The discontinuation rate in this study is similar to the rates of 38% in Bangladesh, 34% in Senegal, 31% in Tanzania and 27% in Ethiopia [ 22 25 ], indicating that Myanmar’s contraceptive discontinuation magnitude is similarly high as other developing countries.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, the 12-month contraceptive discontinuation rate among women age 15–49 who started an episode of contraceptive use within the 5 years before the MDHS was 39% for all methods., This rate was consistent with the average 12-month discontinuation rate (38%) in 25 other low and middle income countries [ 13 ]. The discontinuation rate in this study is similar to the rates of 38% in Bangladesh, 34% in Senegal, 31% in Tanzania and 27% in Ethiopia [ 22 25 ], indicating that Myanmar’s contraceptive discontinuation magnitude is similarly high as other developing countries.…”
Section: Discussionsupporting
confidence: 78%
“…The MDHS results were also consistent with a study from Senegal, in which discontinuation was lower among long-term methods (6 and 18% for implants and IUD, respectively) than for pills (38%) and injectables (33%) [ 23 ]. Likewise in an Ethiopian study, the highest discontinuation rates were found in pill users (38%) while IUD users had the lowest discontinuation rates (14%) [ 25 ]. Short-term method users may discontinue at higher rates because they can stop using their method without the assistance of health providers.…”
Section: Discussionmentioning
confidence: 99%
“…The variations may be due to different population characteristics. However, the prevalence of modern contraceptive utilization in this study was higher than the study conduct in Ofla District, Tigray, Northern Ethiopia (37.1%) [10], in Tigray, North Ethiopia(35.6%) [11], in Humera town, Tigray Region, Ethiopia(27.1%) [12], in Tigray, Ethiopia(46%) [13], in South Nigeria (21.6%) [20]. United Nations millennium development goal (MDG) 2015 report for African continent (33.4%) [2], and the 2015 sub-Saharan MDG reports [2].…”
Section: Discussionmentioning
confidence: 57%
“…Study conduct in Ofla District, Tigray, Northern Ethiopia (37.1%) [10], in Tigray, North Ethiopia(35.6%) [11], in Humera town, Tigray Region, Ethiopia(27.1%) [12], in Tigray,…”
Section: Introductionmentioning
confidence: 99%
“…For example, due to unavailability of contraception about 20% of the unwanted pregnancy occurred in women in refugee camps in Ethiopia, and more than three-quarter of those resulted in maternal mortality (Gebrecherkos et al, 2018). Moreover, a high interruption of modern contraceptive use was observed among reproductive aged Ethiopian women (Belete, Zemene, Hagos, & Yekoye, 2018). Such of many unintended pregnancies, still birth, and neonatal and maternal deaths can be averted by using contraception regularly (Berhan & Berhan, 2014;Godefay, Byass, Graham, Kinsman, & Mulugeta, 2015).…”
Section: Introductionmentioning
confidence: 99%